2013
DOI: 10.1590/jvb.2013.050
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization after acute deep vein thrombosis

Abstract: The process of recanalization of the veins of the lower limbs after an episode of acute deep venous thrombosis is part of the natural evolution of the remodeling of the venous thrombus in patients on anticoagulation with heparin and vitamin K inhibitors. This remodeling involves the complex process of adhesion of thrombus to the wall of the vein, the inflammatory response of the vessel wall leading to organization and subsequent contraction of the thrombus, neovascularization and spontaneous lysis of areas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The same finding in the published literature by Brandao and his colleagues confirms this identification. 3 The phasic Doppler waveform in the proximal vein and the triphasic pulsatile Doppler waveform in the proximal artery confirmed that it was not an arteriovenous fistula. The spectral Doppler waveform of vasa vasorum also showed a flow at a low velocity (50 cm/s), which would be considered quite low for a working arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The same finding in the published literature by Brandao and his colleagues confirms this identification. 3 The phasic Doppler waveform in the proximal vein and the triphasic pulsatile Doppler waveform in the proximal artery confirmed that it was not an arteriovenous fistula. The spectral Doppler waveform of vasa vasorum also showed a flow at a low velocity (50 cm/s), which would be considered quite low for a working arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 73%
“…1,2 When a vein thromboses, vasa vasorum engages in a process of recanalization. 3 The case study published by Brandao and his colleagues suggests that the visualization of vasa vasorum may indicate the process of recanalization may start earlier than how it is documented in most literatures. This current case study identifies vasa vasorum, and confirms its identification by the same findings as in the study by Brandao and his colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…19 Currently, the use of DOACs is recommended by guidelines for the treatment of VTE. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]20 However, there are a few studies showing thrombus resolution after DVT using DOACs.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the DVT treatment is to relieve the symptoms, suppress the progression of thrombus, and prevent pulmonary thromboembolism and other complications secondary to DVT by inducing adequate anticoagulation. 2 After the development of femoropopliteal DVT, the competition between residual venous thrombosis (RVT) and recanalization determines the clinical course of DVT. 3 The extent and duration of the balance created between these 2 factors by DOACs or warfarin, a vitamin K antagonist used in the treatment of DVT, are unclear.…”
Section: Introductionmentioning
confidence: 99%